Review of the National Experience of Measuring Gender Inequality in Ukraine, 2009–2021. Part I. Government Practice of Gender Measurements - Skoryk, M. M. (Statistics of Ukraine, 2022)
The review presents the national practice of measuring gender equality in Ukraine since 2009 and identifies gaps in the tools, methods and indicators used for this measurement. Due to the difference in the powers and responsibilities of governmental and non-governmental sectors, the first part of the review presents state practices for measuring gender inequality, and the second part presents relevant initiatives by non-governmental communities and donors. It is argued that the state gender measurements in Ukraine had two active periods: 2009-2011 and 2019-2021. The first of them introduced the practice of preparing gender portraits of regions, which became widespread; and prepared a basic overview of the feasibility of creating a national system of gender statistics of Ukraine and its indicators. In the second of them, the government carried out work on standardizing the gender profiles of 25 regions of Ukraine; and the selection of gender-disaggregated indicators for nationwide monitoring of gender equality. It has been established that the longest-running and most widespread national practice of gender dimension in Ukraine is gender portraiture, which was conducted in more than 2/3 of Ukraine’s regions and later spread to cities and local communities. However, tools for gender profiling and reporting on sets of advanced indicators have not become widespread. It is established that the predominant type of gender measurement tool is a set of indicators, numbering about 30, grouped in 4-6 thematic areas. This set is usually determined from the available data of the State Statistics Service and is available for use in the absence of professional gender analysts. Attempts to use and disseminate more detailed sex measurement tools have failed. According to the levels of the gender measurement, national and local measurements were found to be preferred. There were no precedents for sectoral gender measurement and attempts to develop sectoral gender statistics. It is concluded that this is a gap that needs to be addressed. It was found that all measurements, except for the statistical collection ‘Women and Men in Ukraine” were irregular. Measurements on the same list of indicators were carried out once or never. It is concluded that there is a lack of coordination of measurement practices at the national and local levels, even if it was carried out by the same responsible state body. The review was prepared within the framework of the Women’s Rights Monitoring Initiative project, implemented in 2019-2021 by the Kyiv Institute for Gender Studies with the support of the Swiss Embassy in Ukraine.